Self-regulating roof-bolting with the rock pressure energy use - Khomenko, Oleh; Kononenko, Maksym; Kovalenko, Ihor; Astafiev, Denys (My University, 2018)
The perspective of discovery of zonal disintegration phenomenon of rocks around underground mine workings is analyzed. The methodological stages for research of this phenomenon are shown. The physics of zonal disintegration of rocks around underground mine workings is disclosed. There are described the possibilities of advanced entropy method and developed energy method that allow to investigate a phenomenon of zonal capsulation of underground mine workings. The sequence of research of this phenomenon parameters is presented. The order of choice of stable shape and resource-saving support in underground mine workings is substantiated, for the deep horizons of the Kryvorizkyi Iron-Ore Basin mines. The method of parameters calculation of self- regulating roof-bolting in underground mine workings is substantiated, which allows to use the rock pressure energy. The design of a self- regulating roof-bolting is developed, which allows applying metal, polymer and rope bolts. The economic efficiency of rock pressure energy usage is substantiated in case of support setting at great depths in underground mine workings.